Global extinction risk for seahorses, pipefishes and their near relatives (Syngnathiformes) - Pollom, Riley A.; Ralph, Gina M.; Pollock, Caroline M.; Vincent, Amanda C.J. (Oryx, 2021)
Few marine taxa have been comprehensively assessed for their conservation status, despite heavy pressures from fishing, habitat degradation and climate change. Here we report on the first global assessment of extinction risk for 300 species of syngnathiform fishes known as of 2017, using the IUCN Red List criteria. This order of bony teleosts is dominated by seahorses, pipefishes and seadragons (family Syngnathidae). It also includes trumpetfishes (Aulostomidae), shrimpfishes (Centriscidae), cornetfishes (Fistulariidae) and ghost pipefishes (Solenostomidae). At least 6% are threatened, but data suggest a mid-point estimate of 7.9% and an upper bound of 38%. Most of the threatened species are seahorses (Hippocampus spp.: 14/42 species, with an additional 17 that are Data Deficient) or freshwater pipefishes of the genus Microphis (2/18 species, with seven additional that are Data Deficient). Two species are Near Threatened. Nearly one-third of syngnathiformes (97 species) are Data Deficient and could potentially be threatened, requiring further field research and evaluation. Most species (61%) were, however, evaluated as Least Concern. Primary threats to syngnathids are (1) overexploitation, primarily by non-selective fisheries, for which most assessments were determined by criterion A (Hippocampus) and/or (2) habitat loss and degradation, for which assessments were determined by criterion B (Microphis and some Hippocampus). Threatened species occurred in most regions but more are found in East and South-east Asia and in South African estuaries. Vital conservation action for syngnathids, including constraining fisheries, particularly non-selective extraction, and habitat protection and rehabilitation, will benefit many other aquatic species.